2020
DOI: 10.1097/scs.0000000000006544
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Treatment for Elderly Patients With Trigeminal Neuralgia: Percutaneous Balloon Compression Versus Microvascular Decompression

Abstract: Objective: The study aimed to evaluate the surgical outcomes of percutaneous balloon compression (PBC) and microvascular decompression (MVD) in the treatment of elderly patients with trigeminal neuralgia (TN). Methods: A total of 30 patients who underwent PBC surgery (PBC group) and 30 patients who received MVD surgery (MVD group) were included. The treatment efficacy, Barrow Neurological Institute (BNI) pain intensity score, inflammatory response, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Although a sizable body of studies demonstrated the importance of objective clinical predictors of curative effect, the selection of TN patients for PBC was still subjective [24,21,18]. Until now, there was no objective scale established for the prediction of TN patients' after PBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a sizable body of studies demonstrated the importance of objective clinical predictors of curative effect, the selection of TN patients for PBC was still subjective [24,21,18]. Until now, there was no objective scale established for the prediction of TN patients' after PBC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the microvascular decompression (MVD) has been widely accepted as an effective remedy for treatment of TN, it needs open-brain surgery and the mortality has been quoted as 0.22-2% [27,11,8,23]. Percutaneous balloon compression (PBC) of a trigeminal ganglion (TG) is an acknowledged alternative with a relatively high pain relief rate, ranging from 70% to over 90% [25,21,18]. Because of its convenience and safety, PBC has become a more popular remedy for trigeminal neuralgia recently.…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen studies (13,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) compared the adverse reaction rates between MVD and PBC cases. The heterogeneity results were I 2 =64% (P=0.0003); thus, the rate of adverse reaction for PBC versus MVD treatment was 17.79 (95% CI: 10.17-31.11; P<0.00001) using the random-effects model.…”
Section: Adverse Reaction Rates After Treatment With Pbc Versus Mvdmentioning
confidence: 99%
“…Other surgeries, such as percutaneous balloon compression (PBC), gamma knife radiotherapy, glycerol rhizotomy, and radiofrequency thermocoagulation, have repeatedly been reported to be useful for pain control in TN for which pharmacological treatments have failed [1,[6][7][8][9]. Among these surgical options, PBC is a commonly used microinvasive technique and shows potential in the control of TN [6,9,10]. However, PBC involves the cannulation of foramen ovale (FO) which requires clinicians to overcome a challenging learning curve and is a very important procedural component [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among these surgical options, PBC is a commonly used microinvasive technique and shows potential in the control of TN [ 6 , 9 , 10 ]. However, PBC involves the cannulation of foramen ovale (FO) which requires clinicians to overcome a challenging learning curve and is a very important procedural component [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%